KERAJAAN ALLAH DALAM DUA WAJAH Datangnya Ratu Adil dan Kerajaan Allah - Stepanus Istata Raharjo (Jurnal Teologi (Journal of Theology), 2014)
The javanese mysticism (Kejawen) reflects a kind of messianic idea of a just king(Ratu Adil)that can be compared to the notion of "God's reign" in Christianity. The concept of "Ratu Adil" had inevitably influenced javanese customs, language system as well as various ritual traditions. Considering that the Kejawen itself is a mixture of various elements from different religious systems (such as Hinduism, Buddhism, and Islam), it is neccessary to trace back sources or traditions, from which the notion of Ratu Adil had been developed. This article aims to discuss and to compare the understanding of "Ratu Adil" with the notion of "God's reign".